Integrating Acoustic Telemetry into a Mark–Recapture Model to Improve Catchability Parameters and Abundance Estimates of Lake Sturgeon in Eastern Lake Erie. (13th August 2019) - Withers, Jonah L.; Einhouse, Donald; Clancy, Michael; Davis, Lori; Neuenhoff, Rachel; Sweka, John
Abstract: Estimating abundances of rare fish species that exhibit low recapture rates can be challenging and can require decades' worth of data to produce reliable results. However, when data sets are limited, auxiliary information used to fix model parameters may improve model outputs if that information is reasonably estimated. We collected mark–recapture data on 195 unique Lake Sturgeon Acipenser fulvescens in eastern Lake Erie near the headwaters of the Niagara River between 2012 and 2018. We ran Jolly–Seber capture–recapture models with the POPAN formulation in Program R using the RMark package to estimate abundance within our study area. Initial model runs produced unreasonable parameters (e.g., >99% survival). To improve our model, we integrated acoustic telemetry presence–absence data to calculate and fix catchability parameters in our model. Integrating acoustic telemetry‐derived catchability parameters in our mark–recapture model produced adult abundance estimates (mean ± SE = 889 ± 184) that might not otherwise have been achieved given our relatively small data set and few recaptures. Our findings demonstrate the potential value of integrating reasonably estimated parameters generated by acoustic telemetry studies into mark–recapture.